Genomic analysis of an Argentinean isolate of Spodoptera frugiperda granulovirus reveals that various baculoviruses code for Lef-7 proteins with three F-box domains - Ferrelli, Maria Leticia (2018)
A new isolate of the Spodoptera frugiperda granulovirus, SfGV ARG, was completely sequenced and analyzed. The SfGV ARG genome is 139,812 bp long and encodes 151 putative open reading frames. Of these ORFs, 56 were found in betabaculoviruses, 19 of which are present only in GVs closely related to SfGV. Seven ORFs found homologs in this small GV group and also in noctuid NPVs. ORF066 codes a 74 amino acid protein, overlapped with nudix gene, with several homologs in baculovirus, found by tblastn search. Comparison with the genome of the Colombian isolate SfGV VG008 resulted in SfGV being 1101 bp smaller and lacking a homologue of VG008 ORF084, which codes for Lef-7. However, we found that ORF051 shows remote homology to Lef-7 proteins. Moreover, analysis of ORF051 along with Lef-7 proteins coded by a group of noctuid specific GVs and NPVs indicated that Lef-7 proteins coded by these viruses include three F-box domains in contrast to the single one reported for AcMNPV Lef-7. SfGV ARG genome also contains a split photolyase as a distinct feature not found in VG008. BlastX analysis revealed that a complete photolyase is coded considering a putative frameshift in a poly-A tract, which resembles known slippery sequences involved in programmed ribosome frameshifting.